Milk Supplementation as a Potential Intervention for Overcoming Anemia and Chronic Energy Deficiency during Pregnancy - Fikawati, Sandra; Syafiq, Ahmad (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed to determine the effect of milk supplementation on Mid-Upper Arm Circumference (MUAC) and hemoglobin level in pregnant women. It is a quasi-experimental study conducted from May to August 2019. The sampling was done by purposive sampling, and 108 pregnant women were recruited and divided into two groups: intervention group and non-intervention group. The intervention group received Fe-fortified milk supplementation, and the non-intervention group received education on anemia prevention. Data were analyzed using paired t-test. The result was that providing milk supplementation to pregnant women for three months could significantly increase MUAC and prevent further decline in hemoglobin levels.